Aberrant brain voxel‐wise resting state fMRI in patients with thyroid‐associated ophthalmopathy. Issue 4 (5th April 2021) - Chen, Wen; Wu, Qian; Chen, Lu; Zhou, Jiang; Chen, Huan‐Huan; Xu, Xiao‐Quan; Wu, Fei‐Yun; Hu, Hao
ABSTRACT: Background and Purpose: Although ophthalmic complaints were mostly mentioned in thyroid‐associated ophthalmopathy (TAO), emotional and psychological disturbances are increasingly concerned. We aimed to investigate the brain functional alteration in TAO patients by using resting‐state functional MRI (rs‐fMRI) with the fractional amplitude of low‐frequency fluctuation (fALFF), regional homogeneity (ReHo), and degree centrality (DC) methods. Methods: Twenty‐one consecutive TAO patients and 21 healthy controls (HCs) underwent rs‐fMRI scans. The fALFF, ReHo, and DC values were compared between groups. Results: Compared with HCs, TAO group showed decreased fALFF values in bilateral calcarine/left lingual gyrus and left middle occipital gyrus (MOG). Moreover, TAO group had decreased ReHo values in left MOG/inferior occipital gyrus/fusiform gyrus, while increased ReHo values in bilateral middle frontal gyrus (MFG)/superior frontal gyrus (SFG) than HCs. TAO group also showed decreased DC values in bilateral postcentral gyrus (PoCG)/precentral gyrus/superior parietal lobule and supplementary motor area, and increased DC values in left SFG/MFG and MFG. In TAO patients, ReHo value in left MOG was positively correlated with visual acuity ( r = 0.524, p = 0.021), while ReHo values in bilateral MFGs were negatively correlated with cognitive scores (left/right: r = –0.476/–0.527, p = 0.039/0.020). DC value in left PoCG was negatively correlated with disease duration ( r = –0.492, p = 0.033). Conclusions: Our findings indicated that TAO patients had brain functional alterations in the visual network, executive control network, sensorimotor network, and attention network, which may reflect potential visual and cognitive dysfunctions.